Congenital Ectropion in Down’s Syndrome: A Case Report - Islam, Md Rafiqul; Akther, Khandokar Urmina; Ghosal, Sharmistha; Siddiqua, Ayesha (Eastern Medical College Journal, 2024)
Congenital bilateral ectropion of the eyelids is a rare, benign condition reported in ophthalmic literature. It is more frequently associated with Down’s syndrome, ichthyosis and sporadic cases in newborns from the black population. A rare case of primary congenital ectropion of all four eyelids in a child with Down’s syndrome is reported to emphasize the problems of surgical management. Congenital ectropion is associated with other eyelid abnormalities and usually requires surgical measures to protect the cornea. Eastern Med Coll J. July 2024; 9 (2): 129-131